A contactless approach for monitoring the mechanical properties of swollen hydrogels. Issue 35 (22nd August 2018) - Ruland, Andres; Chen, Xifang; Khansari, Afsaneh; Fay, Cormac D.; Gambhir, Sanjeev; Yue, Zhilian; Wallace, Gordon G.
Abstract : Using ultrasound, we provide a simple and rapid contactless approach for the mechanical characterization of photocrosslinked hydrogels with swelling properties. Abstract : Using a customized ultrasound setup we investigate the feasibility of using a contactless approach to study the bulk mechanical properties of swollen hydrogels. The study involved two different hydrogels, gelatin methacrylate (GelMa) and green algae extract methacrylate (GAEM), which were prepared to provide materials with varying modulus and different swelling properties. Two approaches have been developed. In the first case, ultrasound was compared to Young's modulus measured by indentation. It was found that can be linearly related to indentation modulus values only when the hydrogel swelling ratio is taken into account. In the second approach, an exponential dependency between swelled thickness and indentation modulus was found. This is representative for each hydrogel and purification method in addition to being independent of the conditions used within the toughness range explored. The results of this study indicate that a simple thickness measurement via the proposed approach can provide a direct relationship to Young's modulus upon calibration.